Yona of the dawn. 38 - Kusanagi, Mizuho, 1979- (Shojo beat manga., 2023)
General Rahn of the Kai Empire engineers a devastating flood that sweeps Hak and the precious senju herbs away! With the Thunder Beast nowhere to be found, an anxious Yona nevertheless intends to join the Four Dragons on the battlefield as the Kohka army summons all the tribes for war!